Zeitschrift für interkulturelle Germanistik (transcript-Verlag, 2010)
Interculturalism has established itself as a leading and innovative category of research both in national and international German language and literature studies. Thus the "ZiG" has become a well-known medium in this discipline. It appears twice a year.